1995
DOI: 10.1111/j.1745-6606.1995.tb00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Comprehension of Environmental Advertising and Labeling Claims

Abstract: Two national surveys, with a total of 2,004 respondents, were conducted to examine comprehension of the terms “recycled” and “recyclable.” Only about five percent of respondents exhibited a thorough understanding of “recycled” and “recyclable” consistent with EPA and FTC definitions. Moreover, respondents displayed a limited understanding of “pre‐consumer waste,” assumed a high percentage of recycled content in products labeled “recycled,” and inferred widespread availability of recycling facilities whenever a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 5 publications
0
57
0
2
Order By: Relevance
“…Two of such studies [135,136] concluded that many consumers having no detailed understanding of the term "recyclable" may confuse the term "recyclable" with "recycled" and may overestimate the likelihood that products labeled "recyclable" will be recycled. Consumers might be misled by the overestimation of the amount of environmental benefit of product advertised if they lack in-depth comprehension [125]. As a result, uncertainty remains with respect to how labels influence consumers and how well consumers comprehend the information provided on product labels [131].…”
Section: Construct Reference Key Argumentmentioning
confidence: 99%
See 2 more Smart Citations
“…Two of such studies [135,136] concluded that many consumers having no detailed understanding of the term "recyclable" may confuse the term "recyclable" with "recycled" and may overestimate the likelihood that products labeled "recyclable" will be recycled. Consumers might be misled by the overestimation of the amount of environmental benefit of product advertised if they lack in-depth comprehension [125]. As a result, uncertainty remains with respect to how labels influence consumers and how well consumers comprehend the information provided on product labels [131].…”
Section: Construct Reference Key Argumentmentioning
confidence: 99%
“…Rather consumers are likely to be uncertain about the meaning of these terms since different manufacturers use these terms based on differing standards [125]. For example, the claim "made from recycled materials" might be interpreted differently by different consumers.…”
Section: Construct Reference Key Argumentmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend for fast-fashion and the lack of standardization in the industry may contribute to the failure for sustainability labelling to be widely adopted (Aspers 2008;Kunz and Garner 2011). Furthermore, the terms or technical jargon used in marketing claims for sustainability apparel products, such as all natural, organic, recyclable, and recycled, and the symbols and logos are sometimes too vague for consumers to understand without specific definitions included (Kim et al 2012;Morris et al 1995). Because term meanings on labels may vary by company, even with efforts by federal and state governments to standardize use of labelling terms, terms are often misinterpreted by consumers (Chen and Burns 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Several consumer researchers participated in the hearings by discussing tracking studies on environmental claim use across product categories and geographical areas (Mayer et al 1995). In addition, an entire issue of the Journal of Advertising (Summer 1995) was devoted to research on environmental marketing claims (see also Morris, Hastak, and Mazis 1995). One of the studies provided a thorough analysis offederal, state, and local agency policies with respect to environmental marketing claim regulation (Scammon and Mayer 1995).…”
Section: Environmental Marketing Claimsmentioning
confidence: 99%